Violence against the Minorities in Bangladesh - Ahmmed, Md Mortuza (Himalayan Journal of Sociology and Anthropology, 2014)
Violent attacks on religious minorities in recent days have evoked popular protests at home and abroad, and the minority community thinks it is an attempt to force them to leave the country like in 1971.They fear the extent of the dreadfulness of attacks on the minorities might exceed what they had seen during 2001 and appealed to the international community apart from the political parties to look into the matter seriously.The situation of minorities in Bangladesh is a human rights issue. Status of minorities all over the world has demonstrated a pattern of discrimination and insecurity. Bangladesh is no exception. However, the example of minorities in Bangladesh has a typical trend. The seeds of violence against the minority community are inherent within the structures of the modern system which has turned human beings into vote banks and vote constituencies. Lack of accountability and transparency of the state machinery only makes the situation worse. Bangladesh ought to recognize the plurality of its culture and people. Undoubtedly, civil society has the major and the most important role to play in this respect. This paper contains the theoretical explanation of the concept of “minority” in general and then examines the state of minorities in Bangladesh, their problems, the violations against them, the factors and impact of violations, state responsibilities, legal and constitutional protection, protection under international law etc. DOI: http://dx.doi.org/10.3126/hjsa.v6i0.10712   Himalayan Journal of Sociology and Anthropology Vol.6 2014: 112-118